Analisis Determinan Kepatuhan Wajib Pajak UMKM di Masa Pandemi Covid-19 - Sulistiyanti, Umi; Az Zahra Fakhrunnisa (Program Sarjana Terapan Universitas Islam Indonesia, 2023)
Tax Compliance of Micro, Small and Medium enterprises (MSMEs) sector is still a problem that must be taken seriously by the government. Especially in the Covid-19 pandemic, there is potential of decrease MSMEs Tax compliances. This research aims to analyze the effect of tax awareness, modernization of the tax administration system, earning turnover and tax incentive policy on tax compliance MSMEs registered as MSME taxpayers at KPP Pratama Purwokerto during the Covid-19 pandemic. This research is quantitative research using primary data. The sampling technique uses purposive sampling method. The research sample amounted to 110 respondents who were considered to represent the population and the research data processed using multiple regression Analysis. The results of this research show that tax awareness has a positive effect on taxpayers compliance of MSMEs while modernization of the tax administration system, earning turnover and tax incentive policy have no effect on taxpayers compliance of MSMEs